HANDLING PROCUREMENT ADMINISTRATION BY PTROYALINDO EXPODUTA FOR ORGANIZING THE SIXTHCONFERENCE OF THE GLOBAL PARLIAMENTARIANS AGAINSTCORRUPTION (GOPAC) - Azmy, Sita Fimalasari; Priyanto, Priyanto (UI Scholars Hub, 2018)
This journal is concerned with the handling of administrative documents required as one of the requirements of PT Royalindo Expoduta for participating in the tender of MICE on the procurement held by the Dewan Perwakilan Rakyat (DPR) through the LPSE website of the Dewan Perwakilan Rakyat. The name of the auction is the Procurement Professional Conference Organizer (PCO) for the Operation of The Sixth Conference Of The Global Parliamentarians Against Corruption (GOPAC). In addition the authors discuss about what strategies need to be prepared to support the success of PT Royalindo Expoduta who became the winner at that time. Describe the constraints and obstacles and the best solution by Tender Division of PT Royalindo Expoduta.